2017
DOI: 10.1172/jci92387
|View full text |Cite
|
Sign up to set email alerts
|

Neural precursor cell–secreted TGF-β2 redirects inflammatory monocyte-derived cells in CNS autoimmunity

Abstract: In multiple sclerosis, the pathological interaction between autoreactive Th cells and mononuclear phagocytes in the CNS drives initiation and maintenance of chronic neuroinflammation. Here, we found that intrathecal transplantation of neural stem/precursor cells (NPCs) in mice with experimental autoimmune encephalomyelitis (EAE) impairs the accumulation of inflammatory monocyte-derived cells (MCs) in the CNS, leading to improved clinical outcome. Secretion of IL-23, IL-1, and TNF-α, the cytokines required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 92 publications
(88 reference statements)
1
30
0
1
Order By: Relevance
“…It is known that eNPCs can regulate microglia density and function as well as its activity by VEGF secretion (Mosher et al, 2012). Thus, we can speculate that in this lesion model the lack of eNPC-secreted growth factors, such as VEGF (Mosher et al, 2012;Bacigaluppi et al, 2016) or TGF-␤ (De Feo et al, 2017), might be responsible for the increased microglia activation.…”
Section: Discussionmentioning
confidence: 76%
“…It is known that eNPCs can regulate microglia density and function as well as its activity by VEGF secretion (Mosher et al, 2012). Thus, we can speculate that in this lesion model the lack of eNPC-secreted growth factors, such as VEGF (Mosher et al, 2012;Bacigaluppi et al, 2016) or TGF-␤ (De Feo et al, 2017), might be responsible for the increased microglia activation.…”
Section: Discussionmentioning
confidence: 76%
“…A follow-up study from the same group demonstrated similar results are observed from transplanted hNSCs derived from induced pluripotent stem cells (iPSCs; Plaisted et al, 2016). Furthermore, a recent study in a non-viral mouse model of MS, experimental autoimmune encephalomyelitis (EAE), demonstrated that mouse embryonic NSC-secreted TGF-β2 inhibits the differentiation of pro-inflammatory monocyte-derived dendritic cells in vivo and in vitro (De Feo et al, 2017).…”
Section: Modulation Of Cellular Responses Nsc-secreted Factors and Immentioning
confidence: 70%
“…By the injection of IL-4 + Mfg-e8 + EVs into liquoral space, we can directly target meningeal resident cells with patrolling activity and newly infiltrating phagocytes, such as monocyte-dendritic cells, which are extensively described as main effector cells in EAE. 30,31 As shown in Figures 6 and 7, using IL-4 + EVs targeted with Mfg-e8, we can induce an anti-inflammatory phenotype in CD11b + cells, similar to gene therapy with IL-4. 14 Myeloid cells in the meningeal compartment and in the choroid plexus have been recently indicated as a crucial checkpoint in human and experimental neuroinflammation.…”
Section: Discussionmentioning
confidence: 84%